1992
DOI: 10.1016/0741-5214(92)90368-i
|View full text |Cite
|
Sign up to set email alerts
|

The evolving surgical management of recurrent carotid stenosis

Abstract: The traditional approach to recurrent carotid stenosis has been repeat endarterectomy or patch angioplasty. Concern with the durability of repeat carotid endarterectomy has resulted in our use of carotid resection with autogenous graft interposition. This study was designed to determine the outcome and efficacy of carotid resection compared with repeat carotid endarterectomy in the management of recurrent carotid stenosis. From 1974 to 1991, 162 operations (repeat carotid endarterectomy 105, carotid resection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 15 publications
5
41
0
3
Order By: Relevance
“…There are only six reports of Ͼ100 procedures, 6,13,16,30,33,36 10 reports of 50 to 99 procedures, 7,14,15,17,19,23,24,27,34,35 and 14 reports of Ͻ49 procedures. 5,18,[20][21][22]25,26,28,29,31,32,37,38 The reported 30-day stroke and death rates range from 0% to 5.4% (Table I).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There are only six reports of Ͼ100 procedures, 6,13,16,30,33,36 10 reports of 50 to 99 procedures, 7,14,15,17,19,23,24,27,34,35 and 14 reports of Ͻ49 procedures. 5,18,[20][21][22]25,26,28,29,31,32,37,38 The reported 30-day stroke and death rates range from 0% to 5.4% (Table I).…”
Section: Discussionmentioning
confidence: 92%
“…Carotid resection with the placement of an interposition graft is another surgical option. 19,30 In our opinion, interposition grafting is a distinct procedure; therefore, it was an exclusion criterion. In the present series, however, two patients with secondary recurrent stenosis received an interposition graft for tertiary revascularization.…”
Section: Discussionmentioning
confidence: 98%
“…Redo is believed to be more difficult than primary CEA because of the dense scarring surrounding the carotid artery and the difficulty in obtaining tissue cleavage planes. Morbidity (including cranial nerve injury) and mortality rates of 8% to 20% after redo CEA have been reported [22][23][24] ; however, several other authorities have reported better results. [25][26][27][28][29][30] Carotid percutaneous transluminal angioplasty and stenting is increasing in popularity and has been advocated by some investigators as an alternative to reoperation for post-CEA carotid stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] This is largely due to the inherent risks in any open reintervention in a previously operated field, such as increased scar tissue, which can obscure tissue planes and make identification of anatomic structures and surgical landmarks more challenging. Reoperation can have morbidity and mortality rates as high as 8% to 20%, [13][14][15][16][17][18][19][20] although recent literature suggests that this is improving. 6,[21][22][23] O'Donnell et al reported on the results from a metaanalysis of six series that showed a 4.2% stroke rate and a 1% mortality rate for redo carotid surgery, and indicated that the incidence of cranial nerve injury in these patients averaged 8.5%.…”
Section: Discussionmentioning
confidence: 99%